Comparative Evaluation of Antimicrobial Photodynamic Therapy Using Methylene Blue (660 nm Diode Laser) and Indocyanine Green (810 nm Diode Laser) in the Management of Chronic Periodontitis: A Clinical and Microbiological Study - Saumya Shankar; Sachin B. Mangalekar; Jeeth Rai; Shashank Vijapure; Shruti Kumbhare; Prasanna Sawant (Journal of Pharmacy and Bioallied Sciences, 2025)
Aim: The purpose of this study was to compare the microbiological and clinical effects of antimicrobial photodynamic therapy (aPDT) in treating chronic periodontitis by using indocyanine green (ICG) with an 810 nm diode laser and methylene blue (MB) with a 660 nm diode laser as adjuncts to scaling and root planing (SRP). Materials and Procedures: In this split-mouth design research, 14 people were recruited. Three sets of treatment sites were randomly assigned: SRP with aPDT utilizing MB or ICG (test groups) and SRP alone (control group). Using real-time polymerase chain reaction (RT-PCR), samples of subgingival plaque were examined for Tannerella forsythia, Porphyromonas gingivalis, and Treponema denticola. Microbiological counts and clinical indicators, such as Russell’s Periodontal Index (RI), Gingival Index (GI), Plaque Index (PI), clinical attachment loss (CAL), and probing depth (PD), were measured at baseline and three months later. Findings: When compared to the control sites, test sites treated with aPDT showed statistically significant improvements in both clinical and microbiological parameters (P < 0.001). Conclusion: MB and ICG photosensitizers combined with antimicrobial photodynamic therapy show great promise as an adjuvant treatment for chronic periodontitis.